Shari’ah and legal analysis on the use of Islamic attributes in food products labelling in Malaysia - Osman, Suraiya (2024)
Malaysia's population, with 63.5% Muslims, presents a substantial market for halal food products. Consuming halal (permissible) and ṭayyib (wholesome) food is a religious obligation for Muslims, fuelling the expansion of the Muslim food industry. To capitalize on this market, manufacturers and food providers leverage various marketing strategies incorporating Islamic attributes, such as 30 Juzu’ Al-Qur’an drinking water, Mi Cap Masjid, P. Ramly Burger, Milo Zamzam drink, and Jus As-Sunnah. These strategies facilitate Muslim consumers in selecting their desired products, yet the uncontrolled use of Islamic attributes has led to significant concerns. Issues include product safety, the integrity of halal status, exploitation of Islam for personal gain, and deviations from faith, resulting in severe implications for Islam. Some providers engage in false and misleading marketing tactics under the guise of Islamic attributes. This study's primary objective is to define Islamic attributes, assess their permissibility from Islamic and legal perspectives, and evaluate the legal mechanisms controlling their misuse in Malaysia's food product labelling and marketing. Additionally, the study proposes enhancements to the existing legal framework and enforcement mechanisms. The research methodology includes library research, content analysis, and in-depth interviews with halal experts in Malaysia, guided by the Theory of Planned Behaviour (TPB), Consumer Behaviour, and Signalling Theory, along with Maqāsid Shari’ah and Saddu Zari’ah principles. Findings reveal that Islamic attributes in labelling and marketing encompass any product or service feature linked to the Muslim religion or Islamic teachings used to attract Muslim consumers. This practice has resulted in several unresolved issues. According to Maqāsid Shari’ah, which emphasizes the protection of religion, life, wealth, intellect, and lineage, the government must establish a specific legal framework to address these concerns, as current laws are insufficient. Malaysia lacks a detailed definition or regulation for Islamic attributes in food product labelling and marketing. Moreover, no specific authority is empowered to oversee this issue. Laws addressing misuse are fragmented and often conflated with halal misuse, leaving specific issues unresolved. While some fatwas, such as those prohibiting terms like ‘Jus As-Sunnah’ and ‘ruqyah,’ exist, they are not comprehensive. Additionally, definitions of deceit and misleading advertising in existing laws are ambiguous. The study strongly recommends developing a specific legal framework and guidelines for using Islamic attributes in food product labelling and marketing. These guidelines would serve as essential references for food producers, enforcement authorities, and consumers, aiding in identifying false or misleading advertising. Enforcement power should be assigned to the Ministry of Domestic Trade, Cooperation and Cost of Living, Malaysian Islamic Development Department (JAKIM), State Islamic Religious Assembly (MAIN), or State Islamic Religious Department (JAIN), as stipulated under the Trade Description Order 2011. Enforcement officers should receive detailed guidelines through circulars. Islam advocates for fair trade practices and prohibits unjust practices, deceit, and harm, aligning with the protection of Maqāsid Shari’ah. The government, as Ulil Amri, is obligated to uphold these principles. Islam should not be treated as a brand and exploited without stringent control.